UPAYA PEMBENTUKAN KARAKTER DISIPLIN SANTRI MELALUI PEMBACAAN SURAT AL-MULK DAN AYAT DUA PULUH BAGI SANTRI PPTQ BAITUL ABIDIN DARUSSALAM - Isqi Faidla Rahmatika; Ngarifin Shidiq; Ahmad Robihan (DAS Institute, 2026)
Abstract One of the religious habituation programs at PPTQ Baitul Abidin Darussalam that supports character education in discipline is the activity of reciting Surah Al-Mulk and Ayat Dua Puluh. This study aims to analyze the process of building santri discipline through that activity. A qualitative descriptive approach was used, with data collected via observation, interviews, and documentation. Data analysis followed three stages: data reduction, data presentation, and drawing conclusions. The findings show that reciting Surah Al-Mulk and Ayat Dua Puluh is conducted routinely every night before sleep, as well as congregationally at specific times. This routine forms an integral part of the santri's consistent and structured worship habits, fostering discipline reflected in obedience to rules, punctual attendance, active participation, and responsibility in maintaining order and reverence during the activity. Keywords: Discipline, Character Education, Surah Al-Mulk, Ayat Dua Puluh.